2022
DOI: 10.1039/d2cc04436f
|View full text |Cite
|
Sign up to set email alerts
|

High-nuclear polyoxovanadates assembled from pentagonal building blocks

Abstract: Three new high-nuclear polyoxovanadates were constructed from pentagonal {WV5(PhPO3)5} molecular building blocks with different configurations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…By virtue of the electron-withdrawing effect, the reaction time required was extended to 25 min, and high products of sulfoxides were obtained. Overall, these catalytic effects indicated that the electronic factors of aromatic sulfides have negligible influence on this catalytic system . Furthermore, diphenyl sulfide also was oxidized when the temperature was increased, but accompanied by relativity low selectivity (Table , entry 9).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…By virtue of the electron-withdrawing effect, the reaction time required was extended to 25 min, and high products of sulfoxides were obtained. Overall, these catalytic effects indicated that the electronic factors of aromatic sulfides have negligible influence on this catalytic system . Furthermore, diphenyl sulfide also was oxidized when the temperature was increased, but accompanied by relativity low selectivity (Table , entry 9).…”
Section: Resultsmentioning
confidence: 96%
“…Overall, these catalytic effects indicated that the electronic factors of aromatic sulfides have negligible influence on this catalytic system. 58 Furthermore, diphenyl sulfide also was oxidized when the temperature was increased, but accompanied by relativity low selectivity (Table 1, entry 9). Additionally, the catalytic oxidation experiment of catalyst 2 was also performed, as illustrated in Table 1, which also exhibit excellent catalytic behavior comparable to 1.…”
Section: ■ Introductionmentioning
confidence: 99%
“…So, 50 min is the optimal combination time between CD and HMRGS. Under the above-mentioned best conditions, 20.0 μL of MB with different concentrations (5,10,15,20,25, and 30 μM) were dropped on the surfaces of HMRGS/CD/1-Au@rGO/GCEs. The DPV peak current intensity of MB/HMRGS/CD/Au-rGO-1/GCE arrives at a platform when the concentration of MB is 20.0 μM (Figure 6c).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…As an important bridge between macroscopic matter and microscopic particles, nanoclusters generally have definite atomic compositions, tunable nanoscale sizes, abundant geometric structures, and unique electronic characteristics, which can endow them with great potential for application in catalysis, energy storage, and biomedicine. Significantly, one of the most representative subfamilies of nanoclusters are polyoxometalates (POMs), which are generally nanosized aggregates generated by early transition-metal ions through oxygen atoms and display variable architectures, special electronic configurations, as well as reversible electron transfer capability. Because of the inseparable correlation between geometrical structures and intrinsic nature, it has been widely acknowledged that some properties of nanoclusters can be deliberately regulated by structure manipulation. , Thus, exploring and discovering new-type POMs with appealing structures and innovative properties have been an appealing topic in cluster science. To achieve this end, one significant strategy to enrich a library of POM databases is to design and search for novel lacunary POM building units (PBUs), whose vacancies can be readily attacked and functionalized with additional functional components, especially metal ions, and thus construct innovative POMs.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Slightly dome-shaped, these building blocks tend to propagate their curvature over multiple units, giving rise to the curved surfaces of the wheels and spheres. [1a] The pentagonal motifs have also been later extended to other group 6 and group 5 metals, as homometallic {M(M 5 )} (M = W, [14] V, [15] Nb [16] ) and heterometallic {Mo/W} 6 [17] and {M(V 5 )} (M = W, Mo, Nb) [15,18] units. Here we would like to demonstrate that, with the introduction of aromatic carboxylates, π-π interactions can inhibit propagation of the pentagonal units into the typical cyclic and spherical shapes, whereby unusual prismatic cage structures composed of near-flat metal oxide panels can be obtained.…”
Section: Introductionmentioning
confidence: 99%